Sandwich structure - MACKE FLORIAN; DOECKER MICHAEL; WIETING JENS; SCHOOTE KLAUS (2012)
The present invention provides a sandwich structure with a core element in honeycomb form and outer layers with carbon fiber and glass fiber layers, the glass fiber layers being applied to the outer sides of the sandwich structure.